2017
DOI: 10.1128/msphere.00199-17
|View full text |Cite
|
Sign up to set email alerts
|

LpxK Is Essential for Growth of Acinetobacter baumannii ATCC 19606: Relationship to Toxic Accumulation of Lipid A Pathway Intermediates

Abstract: Acinetobacter baumannii is a Gram-negative pathogen for which new therapies are needed. The lipid A biosynthetic pathway has several potential enzyme targets for the development of anti-Gram-negative agents (e.g., LpxC). However, A. baumannii ATCC 19606 can grow in the absence of LpxC and, correspondingly, of lipid A. In contrast, we show that cellular depletion of LpxK, a kinase occurring later in the pathway, inhibits growth. Growth inhibition results from toxic accumulation of lipid A pathway intermediates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
(71 reference statements)
1
19
0
Order By: Relevance
“…In addition to discovering a small molecule that targets MsbA, our study provides insights into an important question: Why are certain steps of LPS biogenesis essential in Acinetobacter when it is also known that the entire pathway can be removed? (21,25,27). Our results show that the organism does not down-regulate LPS biosynthesis upon MsbA inhibition although the most frequenct resistance mechanism we observed is to block LPS biosynthesis.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition to discovering a small molecule that targets MsbA, our study provides insights into an important question: Why are certain steps of LPS biogenesis essential in Acinetobacter when it is also known that the entire pathway can be removed? (21,25,27). Our results show that the organism does not down-regulate LPS biosynthesis upon MsbA inhibition although the most frequenct resistance mechanism we observed is to block LPS biosynthesis.…”
Section: Discussionmentioning
confidence: 56%
“…Recently it has been found that several gram-negative pathogens including Acinetobacter can survive without LPS (22)(23)(24). Paradoxically, certain steps of the LPS biogenesis pathway appear to remain essential in Acinetobacter despite the fact that LPS is not essential (25)(26)(27).…”
Section: Validating Conditional Essentiality Of Certain Lps Biogenesimentioning
confidence: 99%
“…This has been attributed to toxic accumulation of pathway intermediates, although other explanations are possible. An essential gene paradox for lipid A biosynthesis was recently reported whereby LpxH and LpxK, which occur later in the biosynthetic pathway, were essential for in vitro growth of A. baumannii ATCC 19606 even though the earlier catalytic enzymes LpxA or LpxC were dispensable in that strain background (i.e., lipid A synthesis is not essential) ( 59 , 60 ). Similar to our observations here, growth of A. baumannii ATCC 19606 downregulated for LpxH or LpxK was restored by an LpxC inhibitor (LpxC inhibitor-dependent growth), and this was associated with reduction of toxic intermediate accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the fact that these intermediates are amphipathic, detergent like compounds (Fig. ) (Richie et al ., ; Wei et al ., ). This work aligns itself with precedents established in E. coli (Garrett et al ., ; Babinski et al ., ).…”
Section: Mechanisms Of Los‐deficiency In a Baumanniimentioning
confidence: 97%
“…The authors report the lptD mutant having intact LOS, suggesting either the cells have a bypass mechanism to get LOS to the outer membrane or A. baumannii is remarkably suited to tolerating internal accumulations of intact LOS. Either outcome would have a significant impact on the field, and warrants further study and examination of these mutants Richie et al, 2016;Wei et al, 2017).…”
Section: Mechanisms Of Los-deficiency In a Baumanniimentioning
confidence: 99%